Pengaruh Sistem Akuntansi, Kompetensi Staf Akuntansi dan Internal Control Terhadap Kualitas Laporan Keuangan Perusahaan - Fibria Anggraini Puji Lestari (Universitas Indraprasta PGRI, 2020)
This study is to determine the effect of the accounting system, staff competence and internal control on the quality of financial statements of transport companies that have go public in Indonesia listed on the Jakarta Stock Exchange. This study uses a sample of ten transportation companies listed on the Jakarta Stock Exchange. While the research method uses research descriptive quantitative analyzed using multiple linear analysis with SPSS 19.0 for windows. The results of this study indicate that accounting system variables (0.209), accounting staff competencies (0.776), and internal control (0.268) have a positive effect on the quality of financial statements made by companies .